Crowd intelligence in independent film productions - Baranova, D.; Lugmayr, Artur (2013)
This paper is devoted to the challenges of independent film production in raising funding. It gives a brief overview of crowdfunding and crowdsourcing methods as one possibility to improvement funding, as well as the process in acquiring funding. We attempt to suggest to improve the traditional film production tecniques and process with crowd intelligence methods. We further describe the appropriate ways of its implementation. The paper reveals the main similarities and differences of the methods as well as it pinpoints to the advantages and disadvantages of their implementation in different cases. Copyright © 2013 ACM.